[Federal Smoking Ban Proposal] - Walter N. Woodson (Tufts Archival Research Center, 2007)
Missing Attachments; Memo to Wayne Ashworth, Harry Bell, Fred Bond, Robert Caldwell, Bruce Flye, Jim Graham, Ray Mackey, Bob Marlowe, Bill Myers, and John Parker from Walter Woodson on proposed executive order banning smoking. Indicates that OMB will return proposal to HHS with many critical comments from federal agencies and offices. Highlights that organized labor was very active in comment process, particularly around collective bargaining issues, as was lobbying with USDA. Comments that order appears dead.